Management basics for information professionals - Evans, G. Edward, 1937-; Alire, Camila A. (Neal-Schuman, an imprint of the American Library Association, 2013)
This book covers the basics of management that librarians beginning their careers should understand. Part 1 looks at the context of managerial activities that influence what managers, in both for-profit and not-for-profit organizations, cannot, can, and should do. Part 2 discusses the skills required to be an effective manager. Part 3 addresses the essential managerial skills that all great managers understand. Part 4 examines how to manage such things as money, technology, and facilities. Part 5 presents some insights into managing yourself and your career. The third edition includes new sections dealing with innovations in technology and in the economic environment in which libraries must operate.